Investigation of the inhibitors of histone-lysine N-methyltransferase SETD2 for acute lymphoblastic leukaemia from traditional Chinese medicine. Issue 7 (2nd July 2016) - Chang, Y.-L.; Chen, H.-Y.; Chen, K.-B.; Chen, K.-C.; Chang, K.-L.; Chang, P.-C.; Chang, T.-T.; Chen, Y.-C.
Abstract: Leukaemia is the leading cause of childhood malignancies. Recent research indicates that the SETD2 gene is associated with acute lymphoblastic leukaemia. This study aims to identify potential lead compounds from traditional Chinese medicine (TCM) using virtual screening for SET domain containing 2 (SETD2) protein against acute lymphoblastic leukaemia. Docking simulation was performed to determine potential candidates which obtain suitable docking poses in the binding domain of the SETD2 protein. We also performed molecular dynamics (MD) simulation to investigate the stability of docking poses of SETD2 protein complexes with the top three TCM candidates and a control. According to the results of docking and MD simulation, coniselin and coniferyl ferulate have high binding affinity and stable interactions with the SETD2 protein. Coniselin is isolated from the alcoholic extract of Comiselinum vaginatum Thell. Coniferyl ferulate can be isolated from Angelica sinensis, Poria cocos (Schw.) Wolf, and Notopterygium forbesii . Although S-adenosyl-L-homocysteine has more stable interactions with key residues in the binding domain than coniselin and coniferyl ferulate during MD simulation, the TCM compounds coniselin and coniferyl ferulate are still potential candidates as lead compounds for further study in the drug development process with the SETD2 protein against acute lymphoblastic leukaemia.